2011
DOI: 10.1016/j.mambio.2011.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Sexual shape dimorphism in Serbian roe deer (Capreolus capreolus L.)

Abstract: a b s t r a c tThe focus of studies of sexual dimorphism has been mainly on size whereas shape has remained largely ignored when assessing population differentiation. In order to extract exclusive information about shape variability, we combined multivariate statistical procedures with geometric morphometrics and visualization techniques (thin plate splines). All roe deer skulls, used in this study, originated from a single population in Serbia. Our results showed statistically significant sexual dimorphism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In this study, we found that the conversion factor allowed us to get additional parameters which were inserted into the classical biometric database and then analyzed to obtain information about the wildlife population status. These parameters can be correlated with a lot of different features such as age [1,13], sex [13,22,23], geographical features factors [6,24], population density [5], and trophic resource availability [13]. Moreover, the availability of this conversion factor can be useful in the acquisition of measures that could be missing from the database of measures obtained using a caliper due to, for example, a distraction or forgetfulness of the measurement collectors.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the conversion factor allowed us to get additional parameters which were inserted into the classical biometric database and then analyzed to obtain information about the wildlife population status. These parameters can be correlated with a lot of different features such as age [1,13], sex [13,22,23], geographical features factors [6,24], population density [5], and trophic resource availability [13]. Moreover, the availability of this conversion factor can be useful in the acquisition of measures that could be missing from the database of measures obtained using a caliper due to, for example, a distraction or forgetfulness of the measurement collectors.…”
Section: Discussionmentioning
confidence: 99%
“…Our interest in broad-scale, cross-taxonomic comparisons of cranial morphology constrained our choice of landmarks to those that could be accurately identified in many different species (e.g., Ruta et al, 2013 ; Goswami, Milne & Wroe, 2011 ; Wroe & Milne, 2007 ; Goswami, 2006 ). In contrast, studies that use skulls to characterise morphological variation within species (e.g., Blagojević & Milošević-Zlatanović, 2011 ; Giannini et al, 2010 ; Flores, Abdala & Giannini, 2010 ; Bornholdt, Oliveira & Fabián, 2008 ) or to delineate species boundaries within a clade (e.g., Panchetti et al, 2008 ) tend to focus on more detailed, biologically homologous landmarks ( Zelditch, Swiderski & Sheets, 2012 ). Repeating our analyses with a narrower taxonomic focus may give greater insight into the specific morphological differences among subgroups of tenrecs and golden moles.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies that use skulls to characterise morphological variation within species (e.g. Blagojević and Milošević-Zlatanović, 2011;Giannini et al, 2010;Flores et al, 2010;Bornholdt et al, 2008) or to delineate species boundaries within a clade (e.g. Panchetti et al, 2008) tend to focus on more detailed, biologically homologous landmarks (Zelditch et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…While the skull is widely regarded as a good model for studying morphological variation (e.g. Blagojević and Milošević-Zlatanović, 2011;Flores et al, 2010;Giannini et al, 2010)…”
Section: Discussionmentioning
confidence: 99%